Understanding Cannabis sativa L.: Current Status of Propagation, Use, Legalization, and Haploid-Inducer-Mediated Genetic Engineering - David Charles Simiyu; Jin Hoon Jang; Ok Ran Lee (Plants, 2022)
Cannabis sativa L. is an illegal plant in many countries. The worldwide criminalization of the plant has for many years limited its research. Consequently, understanding the full scope of its benefits and harm became limited too. However, in recent years the world has witnessed an increased pace in legalization and decriminalization of C. sativa. This has prompted an increase in scientific studies on various aspects of the plant’s growth, development, and use. This review brings together the historical and current information about the plant’s relationship with mankind. We highlight the important aspects of C. sativa classification and identification, carefully analyzing the supporting arguments for both monotypic (single species) and polytypic (multiple species) perspectives. The review also identifies recent studies on suitable conditions and methods for C. sativa propagation as well as highlighting the diverse uses of the plant. Specifically, we describe the beneficial and harmful effects of the prominent phytocannabinoids and provide status of the studies on heterologous synthesis of phytocannabinoids in different biological systems. With a historical view on C. sativa legality, the review also provides an up-to-date worldwide standpoint on its regulation. Finally, we present a summary of the studies on genome editing and suggest areas for future research.